NanoSIMS imaging reveals metabolic stratification within current-producing biofilms - Chadwick, Grayson L.; Otero, Fernanda Jiménez; Gralnick, Jeffrey A.; Bond, Daniel R.; Orphan, Victoria J. (Proceedings of the National Academy of Sciences - PNAS, 2019)
Metal-reducing bacteria direct electrons to their outer surfaces, where insoluble metal oxides or electrodes act as terminal electron acceptors, generating electrical current from anaerobic respiration. Geobacter sulfurreducens is a commonly enriched electricity-producing organism, forming thick conductive biofilms that magnify total activity by supporting respiration of cells not in direct contact with electrodes. Hypotheses explaining why these biofilms fail to produce higher current densities suggest inhibition by formation of pH, nutrient, or redox potential gradients; but these explanations are often contradictory, and a lack of direct measurements of cellular growth within biofilms prevents discrimination between these models. To address this fundamental question, we measured the anabolic activity of G. sulfurreducens biofilms using stable isotope probing coupled to nanoscale secondary ion mass spectrometry (nanoSIMS). Our results demonstrate that the most active cells are at the anode surface, and that this activity decreases with distance, reaching a minimum 10 μm from the electrode. Cells nearest the electrode continue to grow at their maximum rate in weeks-old biofilms 80-μm-thick, indicating nutrient or buffer diffusion into the biofilm is not rate-limiting. This pattern, where highest activity occurs at the electrode and declines with each cell layer, is present in thin biofilms (<5 μm) and fully grown biofilms (>20 μm), and at different anode redox potentials. These results suggest a growth penalty is associated with respiring insoluble electron acceptors at micron distances, which has important implications for improving microbial electrochemical devices as well as our understanding of syntrophic associations harnessing the phenomenon of microbial conductivity.